Evaluating Heavy Metal Pollution in Nigerian Coal: Enrichment Factors, Pollution Indices and Environmental Implications - Uloko, Felix Omachoko; Agu, Matthew Nnamdi; Agomuo, John Chidowerem; Joseph, Instifanus Abaleni (Journal of Science Research and Reviews, 2025)
Heavy metal pollution is a significant environmental concern in Nigeria, particularly in coal deposits. This study evaluates the level of heavy metal pollution in Nigerian coal deposits using enrichment factors and pollution indices. Coal samples were collected from Maganga, Gboko, Onyeama, Okobo, Opoko-Obido, Odagbo and Ofugo coal fields, and the concentrations of lead, arsenic, chromium, manganese, nickel, cobalt, strontium, antimony and barium were determined. The results showed significant levels of heavy metal pollution, with enrichment factors indicating anthropogenic sources. Pollution indices reveal moderate to high levels of pollution. The study highlights the need for effective environmental management and pollution control measures to mitigate the environmental and health risks associated with the heavy metal pollution in Nigerian coal deposits.